2009
DOI: 10.1161/atvbaha.109.193532
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Analyses of Molecular Haplotypes of the Human Osteoprotegerin Gene Promoter

Abstract: Objective— Osteoprotegerin (OPG) has been reported to be involved in the development of atherosclerotic disease, and OPG gene variation has been associated with plasma OPG levels and different cardiovascular disease phenotypes. However, the genetic architecture of the OPG promoter and its transcriptional regulation are poorly characterized. Methods and Results— We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Our observations were supported by a higher frequency of the TT genotype in postmenopausal women with low BMD suggesting that C950T affects bone mass by decreasing OPG expression by osteoblasts/stromal cells in the bone microenvironment. These results agree with those reported by Hagedorn et al (2009), where it was shown that transcriptional factor early growth response (Egr)-1 binds exclusively to the T allele, preventing specific protein (Sp)-1 binding and thus acting as a repressor. However, SNP C950T alleles were not always correlated with serum OPG levels and bone mass, since systemic OPG could be independently influenced by a number of other factors (Ueland et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Our observations were supported by a higher frequency of the TT genotype in postmenopausal women with low BMD suggesting that C950T affects bone mass by decreasing OPG expression by osteoblasts/stromal cells in the bone microenvironment. These results agree with those reported by Hagedorn et al (2009), where it was shown that transcriptional factor early growth response (Egr)-1 binds exclusively to the T allele, preventing specific protein (Sp)-1 binding and thus acting as a repressor. However, SNP C950T alleles were not always correlated with serum OPG levels and bone mass, since systemic OPG could be independently influenced by a number of other factors (Ueland et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, it has been very recently reported that the OPG -163 T/C may not affect the expression of the OPG gene 6 , however this was an isolated in vitro report. In this context, there are more SNPs located on the OPG gene 13 , However the data on their functionality and mutual relationships are mostly limited to non-Caucasian populations 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…It spans 29 kb and consists of 5 exons, 4 introns, and is transcribed into four transcripts, 2.4 kb one representing the major transcript 12 . There is a degree of genetic variation in the gene with at least 10 SNP localised mostly within the 5´flanking region and also exons/introns 13 . A plausible contribution of a genetic variation in the OPG gene to PJI has so far been investigated only in a single centre and with inconsistent results 9,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Probe sequences corresponding to the −462 G>A variant in the PPP2R2D promoter region were 5′-biotin-GAATATTACATTGTACAGAA G CCAACAAAAGTTATTGCATAG-3′ for −462 G, and 5′-biotin-GAATATTACATTGTACAGAA A CCAACAAAAGTTATTGCATAG-3′ for −462 A. The consensus sequence of the 5′-biotin-labeled double-stranded probe designed to recognize transcription factor NF1 was 5′-GGGCTAGATGGCTGCCAGCCAAGGCTTCAT-3′ [21]. All labeled and unlabeled oligonucleotides were ordered from Sangon Biotech Co., Ltd (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%